Intercity Express Bus Safety Design Issues in Peninsular Malaysia - Majid, Ahmad Zuhairi Abdul; Ibrahim, Siti Zubaidah (2017)
The purpose of this paper is to provide a study on passengers' safety for intercity express bus and road crashes data trends starting from 2003 until 2017.The study focused on the rate of injuries and deaths of intercity express buses passengers.